Construction and validation of a prognostic nomogram in metastatic breast cancer patients of childbearing age: A study based on the SEER database and a Chinese cohort - Ma, Xiang; Xing, Yapeng; Li, Zeying; Qiu, Shun; Wu, Wenzhao; Bai, Jinfeng (Frontiers in Oncology, 2022)
Cancer in patients of childbearing age continues to become increasingly common. The purpose of this study was to explore the impact of metastatic breast cancer (MBC) on overall survival (OS) and cancer-specific survival (CSS) in patients of childbearing age and to construct prognostic nomograms to predict OS and CSS. Data from patients of MBC patients of childbearing age with were obtained from the Surveillance, Epidemiology, and End Results (SEER) database between 2010 and 2015 and the patients were randomly assigned into training and validation cohorts. Univariate and multivariate Cox analyses were used to search for independent prognostic factors impacting OS and CSS and these data were used to construct nomograms. The concordance index (C-index), area under the curve (AUC) curve and calibration curves were used to determine the predictive accuracy and discriminative ability of the nomograms. Additional data were obtained from patients at the Yunnan Cancer Hospital to further verify the accuracy of the nomograms. A total of 1700 MBC patients of childbearing age were identified from the SEER database and an additional 92 eligible patients were enrolled at the Yunnan Cancer Hospital. Multivariate Cox analyses identified ten prognostic factors for OS and CSS that were used to construct nomograms. The calibration curve for the probabilities of OS and CSS showed good agreement between nomogram prediction and the clinical observations. The C-index of the nomogram for OS was 0.735 (95% CI=0.725-0.744), the AUC (ROC curve) at 3 years was 0.806 and 0.794 at 5 years. The nomogram predicted that the C index of the CSS was 0.740 (95% CI=0.730-0.750), the AUC (ROC curve) at 3 years was 0.811 and 0.789 at 5 years. The same results were observed in the validation cohort. Kaplan–Meier curves comparing the low, medium and high-risk groups showed strong prediction results for the prognostic nomogram. We identified several independent prognostic factors and constructed nomograms to predict OS and CSS for MBC patients of childbearing age. These prognostic models should be considered in clinical practice to individualize treatments for this group of patients.